IFNγ-Induced MHC Class II Expression on Islet Endothelial Cells Is an Early Marker of Insulitis but Is Not Required for Diabetogenic CD4+ T Cell Migration - Scott, Nicholas A.; Zhao, Yuxing; Krishnamurthy, Balasubramanian; Mannering, Stuart I.; Kay, Thomas W. H.; Thomas, Helen E. (Frontiers in Immunology, 2018)
Diabetogenic T cells infiltrate the pancreatic islets by transmigrating across the microcapillaries residing close to, or within, the pancreatic islets. Deficiency in IFNgamma signaling prevents efficient migration of T cells into the pancreatic islets, but the IFNgamma-regulated molecules that mediate this are uncertain. Homing of autoreactive T cells into target tissues may require antigen specificity through presentation of cognate antigen by MHC expressed on the vascular endothelium. We investigated the hypothesis that IFNgamma promotes the migration of islet antigen-specific CD4+ T cells by upregulating MHC class II on islet endothelial cells (IEC), thereby providing an antigen-specific signal for islet infiltration. Upon IFNgamma stimulation, MHC class II, which is not constitutively expressed on IEC, was induced. IFNgamma-dependent upregulation of MHC class II was detected in IEC isolated from prediabetic NOD mice at the earliest stages of insulitis, before other markers of inflammation were present. Using a CD4+ T cell-mediated adoptive transfer model of autoimmune diabetes we observed that even though diabetes does not develop in recipient mice lacking IFNgamma receptors, mice with MHC class II-deficient IEC were not protected from disease. Thus, IFNgamma-regulated molecules, but not MHC class II or antigen presentation by IECs is required for the early migration of antigen-specific CD4+ T cells into the pancreatic islets.